Immigrant entrepreneurs and their perceived success in small retail businesses: preliminary New Zealand findings - Nel, Pieter; Abdullah, Moha Asri (2016)
As international migration continues to be a significant force in globalization, some migrants are forced by circumstances to migrate. Others are attracted by the prospects of greater economic, social, and educational opportunities for themselves and their families. Whilst many migrants take up positions in paid employment, a considerable proportion of them migrate specifically to initiate new venture start-up activities. This study highlights preliminary findings on attributes and essential elements of immigrant entrepreneurs, their issues and how they perceived their business success in small retail business. A survey comprising 262 immigrant entrepreneur respondents in Auckland, New Zealand was executed. The study found that about 40 percent had prior business experience before migrating to New Zealand with more than 30 percent migrating with a business visa. An ANOVA test conducted confirms that there are certain issues such as local business regulations, access to capital, advisory services, training facilities and access to suppliers that are important factors contributing to the perceived business success among immigrant entrepreneurs. The outcome of the study will help the training and development authorities to take the necessary steps to outline a new and productive content for potential entrepreneurial development.